Amphiphilic graphene quantum dots as a new class of surfactants. (November 2019) - Xi, Fengna; Zhao, Jingwen; Shen, Chao; He, Jingbo; Chen, Jie; Yan, Yibo; Li, Kaixin; Liu, Jiyang; Chen, Peng
Abstract: Graphene quantum dots (GQDs) are the latest addition to nanocarbon materials family and promise a wide spectrum of novel applications. Herein, we demonstrate amphiphilic GQDs as a new class of zero-dimensional (0D) inorganic surfactants. Amphiphilic GQDs are synthesized using a facile one-step hydrothermal process and exhibit single-layer graphene structure, high crystallinity, uniform size and bright photoluminescence. Owning to ultrasmall size and unique surface-active characteristics, amphiphilic GQDs are able to stabilize Pickering emulsion, self-assemble into self-supporting monolith, disperse hydrophobic carbon nanotubes to form ultra-light aerogel, promote fast spreading of water on superhydrophobic surface. Furthermore, GQD surfactants can mediate Pickering interfacial reactions, such as, polymerization to form hollow microspheres and chemical conversion catalyzed by acidic functional groups on GQD surface. Graphical abstract: Image 1